ANALYSIS OF THE EFFICIENCY OF A THERAPEUTIC PROGRAM USING 10.2-MEV FAST NEUTRONS. OPTIMIZATION AND PROSPECTS OF THE DEVELOPMENT OF A PROCEDURE FOR COMBINED PHOTON-NEUTRON THERAPY. THE EXPERIENCE OF THE URAL CENTER FOR NEUTRON THERAPY - E. Yu. Kandakova; E. A. Pryakhin; A. V. Vazhenin; G. N. Rykovanov; E. P. Magda; G. V. Mokichev; Z. Z. Munasipov; A. I. Kuznetsova; I. A. Vazhenin (Опухоли головы и шеи, 2015)
The Ural Center for Neutron Therapy performs combined photon-neutron therapy for cancer patients, by applying an ELLIT-80 gamma unit and a NG-12I neutron generator. After modernization of the NG-12I generator, there was a need for redetermination of the relative biological efficiency (RBE) to optimize radiotherapy for the patients. An exotest was used to experimentally estimate RBE according to the survival criteria for stem hematopoietic cells in CBA mice after modernization of the equipment generated by the NG-12I unit with respect to the gamma radiation generated by the ELLIT-80 unit. The investigation established that the RBE factor of NG-12I unit-induced radiation determined as the ratio of equally effective doses (our study used D0) was 1.53 for an acute radiation regimen. During fractional radiation, the RBE factor of neutron radiation was 3.05. That is to say, the total neutron radiation dose replacing 20 % gamma radiation (13 Gy) in the used photon-neutron therapy regimen is 4.26 Gy. The experimental findings have led us to conclude that the previously described neuron therapy regimen may be optimized, by increasing the contribution of neutrons to the total course of radiotherapy in a definite category of patients with radioresistant tumors of the head and neck.